Pre-Variscan palaeogeographical structures in the Cantabrian Zone, Spain: some critical considerations regarding their origin, location and significance - van Loevezijn, Gerard B.S. (Geologos, 2023)
An update of the main Devonian pre-Variscan palaeogeographical features of the southern Cantabrian Zone is presented. The approximal locations of these features are recorded in sections studied, with thin, incomplete developments for the highs and thick successions for the troughs. Generally, pre-Variscan palaeogeographical features were affected by Variscan and Alpine orogenic deformations, but with a different impact. Oroclinal bending, tectonic shortening by thrusts, movements along strike-slip faults and bending by folds all affected the Devonian palaeogeographical features, and only an approximation of their location and shape can be given. Nevertheless, the palaeogeography recorded in pre-Variscan sedimentary successions and their relative positions, provide specific, clear and objective evidence of the pre-Variscan elements.